Development Physics Module Based on Project Based Learning Integrated with Local Wisdom on Rotational Dynamics and Equilibrium of a Rigid Body - Fitratul Hayana Habibah; Hidayati Hidayati; Renol Afrizon; Amali Putra; Putri Dwi Sundari (Universitas Negeri Padang, 2023)
Teaching aids are a component of learning. Teaching aids are resources for both teachers and students. However, in reality, teachers who continue to employ the direct learning paradigm have limited access to educational resources and achieve poor student learning outcomes, for example, while teaching rotational dynamics and rigid body equilibrium. This study intends to assess the viability of a project-based physics module for senior high school class XI's rotational dynamics and equilibrium of a rigid body. This kind of research is known as design research. The research techniques used were self-evaluation assessment sheets, expert validation sheets. The product validation data analysis approach employs Aiken's V index. Research findings indicate that the rigid body project-based learning module on rotational dynamics and equilibrium has an astounding average module validation grade of 0.83 in the very good. The rotational dynamics and equilibrium of a rigid body material project-based learning combined with local knowledge module for physics may therefore be inferred to be appropriate for usage by instructors and students throughout the learning process